A study on Student's Challenges and Problems in Learning English Vocabulary (The International Journal for Scientific Research, 2024)
Students deal with a variety of issues that keep them from developing their English language proficiency. One of the most prevalent is their proficiency in vocabulary. The purpose of this study was to determine the challenges participants faced when acquiring vocabulary and the approaches they employed to overcome those challenges. In the second semester of 2024, the researcher gave a questionnaire to every male and female student enrolled in King Faisal University's Applied College in English 101 and 102 to find out about their most common vocabulary problems. The twenty-question questionnaire covers a wide range of topics, including the respondent's difficulties with vocabulary learning and their approaches to overcoming such difficulties. According to the study, learning vocabulary can be hampered by a number of factors, including difficulty pronouncing and spelling English words correctly, difficulty building vocabulary, difficulty applying vocabulary correctly, and difficulty grasping its meaning.
Keywords: Learning Vocabulary; EFL Students; Challenges in Learning Vocabulary